THE METHOD OF PROJECTS IN TEACHING ENGLISH: THE RELATIONSHIP OF STUDY AND PRACTICE - Nargiza , Xalbayevna Babadjanova (Innovative Development in Educational Activities, 2023)
With the advancement of modern technologies, information and knowledge play a larger role in all areas of social development. Owning the knowledge in your native tongue is insufficient for the expert. As a result, the activity-based approach to teaching foreign languages is the best way to ensure that the learning process is as relevant to the trainee’s potential professional employment as possible. We refer to applying various problem-solving techniques. They are research, search, contested methods, and a project approach that combines all of the aforementioned methods.